2012
DOI: 10.1523/jneurosci.6363-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

TRPC5 Channel Is the Mediator of Neurotrophin-3 in Regulating Dendritic Growth via CaMKII  in Rat Hippocampal Neurons

Abstract: Neurotrophin-3 (NT-3) plays numerous important roles in the CNS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 80 publications
1
27
0
Order By: Relevance
“…It has been speculated that by allowing different patterns of Ca 2ϩ influx, diverse TRPC channels may perform distinct regulatory functions in neurons. Indeed, a recent study demonstrated that TRPC5-mediated Ca 2ϩ elevation activates CaMKII␣, whereas TRPC6-mediated Ca 2ϩ elevation activates CaMKIV, resulting in inhibition and promotion of neuronal dendritic growth, respectively (42). In our experiments, it is likely that at presynaptic sites TRPC3 forms heteromers with TRPC6 and is activated by BDNF, allowing Ca 2ϩ influx and resulting in higher intracellular Ca 2ϩ at the synaptic sites, which leads to more mitochondrial docking at synaptic sites regardless of anterograde or retrograde movement of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that by allowing different patterns of Ca 2ϩ influx, diverse TRPC channels may perform distinct regulatory functions in neurons. Indeed, a recent study demonstrated that TRPC5-mediated Ca 2ϩ elevation activates CaMKII␣, whereas TRPC6-mediated Ca 2ϩ elevation activates CaMKIV, resulting in inhibition and promotion of neuronal dendritic growth, respectively (42). In our experiments, it is likely that at presynaptic sites TRPC3 forms heteromers with TRPC6 and is activated by BDNF, allowing Ca 2ϩ influx and resulting in higher intracellular Ca 2ϩ at the synaptic sites, which leads to more mitochondrial docking at synaptic sites regardless of anterograde or retrograde movement of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were treated with the following reagents: ethylene glycol tetraacetic acid (EGTA), SKF96365, mibefradil, nimodipine, D(−)-2-amino-5-phosphonopentanoic acid (D-APV), 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX), cobalt chloride (CoCl 2 ), 1-oleoyl-2-acetyl-sn-glycerol (OAG), thapsigargin, 2-aminoethyl diphenylborinate (2-APB), MG132 and dimethyloxalylglycine N-(methoxyoxoacetyl)-glycine methyl ester (DMOG), all purchased from Sigma; U73122 from Calbiochem; suramin from Santa Cruz Biotechnology; pazopanib, canertinib dihydrochloride and BMS-754807 from MedChem Express; and K252a from Merck. The 3-nitrocoumarin and 7-OH-3-nitrocoumarin were gifts from Renata Tisi and Enzo Martegani (Milano-Bicocca University, Milan, Italy) (He et al, 2012). Recombinant human IGF-1 was from PeproTech.…”
Section: Cell Cultures Reagents and Antibodiesmentioning
confidence: 99%
“…In neuronal cell development, establishment of morphological and functional polarity of dendrites and an axon are crucial in the formation of neural circuits and for efficient transmission of information across neurons (Gomez 2005). Recent findings define a novel function for TRPC5 that TRPC5 regulate dendrite morphogenesis in neurons and connectivity in the brain (He et al 2012;Puram et al 2011). Additionally, TRPC5 contributes to promote axon formation through activating the CaMKK/CaMKIγ cascade in cultured hippocampal neurons (Davare et al 2009).…”
Section: Introductionmentioning
confidence: 99%